Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Examining indicators of hunter-gatherer mobility in arid environments: The example of the final Middle Paleolithic site of Besor 37 (Northern Negev, Israel) - Mae Goder-Goldberger; Onn Crouvi; Elisabetta Boaretto; Lotan Edeltin; Liora Kolska Horwitz; Oriol López-Bultó; Yael Jacoby-Glass; Ron Lavi; João Marreiros; Eduardo Paixão; Naomi Porat; Tami Zilberman; et al. (Archaeological and Anthropological Sciences, 2026)
Besor 37 is an open-air site in the northwestern Negev Desert (Israel). Excavations at the site in 2020 uncovered a rich, in situ Middle Paleolithic assemblage composed of flint and limestone artifacts, animal bones and charcoal. The good preservation of the site is due to its rapid burial by overbank deposition of fluvially reworked loess. Dating using both Optically Stimulated Luminescence and 14 C suggests an average age of 46.6 ± 2.4 ka. Using a macro and micro-archaeological approach, we determined the technological organization and the nature of occupation with reference to spatial patterning of the assemblages. To integrate the site into a regional perspective we used comparative data from four other Late Middle Paleolithic sites, also located in the southern Levantine desert region; Far’ah II, Rosh Ein Mor, Nahal Dimona 24 and Tor Faraj. We evaluate measures of curation, artifact density and assemblage composition to define site type and mobility system. We propose that Besor 37 represents an ephemeral residential occupation, frequented repeatedly by high mobility hunter-gatherers, possibly part of a larger seasonal, perhaps circular mobility pattern.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

The Effect of Environmental Dredging of Muck on an Assemblage of Benthic Amphipods - Nayan Mallick; Kevin B. Johnson; Charles A. Jacoby (Journal of Marine Science and Engineering, 2023)
To yield environmental benefits, fine sediments with ~10% organic matter, termed muck, were dredged from a tributary to the Indian River Lagoon. Key changes were documented by sampling amphipods, sediments, and the water column near the bottom before dredging, and approximately one month and one year after dredging. Overall, muck yielded the fewest taxa, muck or sediments in creeks that were dredged yielded a moderate number of taxa, and undisturbed sediments in the lagoon yielded the highest number of taxa. Amphipods did not appear in areas with muck until one month and one year after dredging. In contrast, amphipods in sediments that were not muck decreased after dredging. Increases in the occurrence of amphipods paralleled increases in concentrations of dissolved oxygen and decreases in the water, silt/clay, and organic content of sediments. Overall, results indicated that conditions for amphipods were improved by removing muck, and that dredging sandier sediment led to decreased taxonomic richness and numbers of amphipods, which resembled the effects of navigational dredging. Thus, this study suggested that managers should consider the type of sediment to be dredged when permitting projects.

The movement ecology of fishes - Steven J. Cooke; Jordanna N. Bergman; William M. Twardek; Morgan L. Piczak; Grace A. Casselberry; Keegan Lutek; Lotte S. Dahlmo; Kim Birnie‐Gauvin; Lucas P. Griffin; Jacob W. Brownscombe; Graham D. Raby; Emily M. Standen; et al. (Journal of Fish Biology, 2022)
Movement of fishes in the aquatic realm is fundamental to their ecology and survival. Movement can be driven by a variety of biological, physiological and environmental factors occurring across all spatial and temporal scales. The intrinsic capacity of movement to impact fish individually ( e.g. , foraging) with potential knock‐on effects throughout the ecosystem ( e.g. , food web dynamics) has garnered considerable interest in the field of movement ecology. The advancement of technology in recent decades, in combination with ever‐growing threats to freshwater and marine systems, has further spurred empirical research and theoretical considerations. Given the rapid expansion within the field of movement ecology and its significant role in informing management and conservation efforts, a contemporary and multidisciplinary review about the various components influencing movement is outstanding. Using an established conceptual framework for movement ecology as a guide ( i.e. , Nathan et al. , 2008: 19052), we synthesized the environmental and individual factors that affect the movement of fishes. Specifically, internal ( e.g. , energy acquisition, endocrinology, and homeostasis) and external (biotic and abiotic) environmental elements are discussed, as well as the different processes that influence individual‐level (or population) decisions, such as navigation cues, motion capacity, propagation characteristics and group behaviours. In addition to environmental drivers and individual movement factors, we also explored how associated strategies help survival by optimizing physiological and other biological states. Next, we identified how movement ecology is increasingly being incorporated into management and conservation by highlighting the inherent benefits that spatio‐temporal fish behaviour imbues into policy, regulatory, and remediation planning. Finally, we considered the future of movement ecology by evaluating ongoing technological innovations and both the challenges and opportunities that these advancements create for scientists and managers. As aquatic ecosystems continue to face alarming climate (and other human‐driven) issues that impact animal movements, the comprehensive and multidisciplinary assessment of movement ecology will be instrumental in developing plans to guide research and promote sustainability measures for aquatic resources.

High Densities of a Prochlorophyte (Unresolved Species) Inhibit Grazing by the Herbivorous Copepod Parvocalanus crassirostris - Xiao Ma; Charles A. Jacoby; Kevin B. Johnson (Frontiers in Marine Science, 2021)
Harmful algal blooms (HABs) are increasing in frequency and severity, underscoring the importance of understanding potential top-down controls of blooms. In the Indian River Lagoon (IRL), a shallow subtropical estuary, one harmful bloom was co-dominated by an unresolved prochlorophyte in the Family Prochlorothricaceae, which reached densities of > 10 6 cells ml –1 engendering the term “Superbloom.” Experiments were conducted to evaluate grazing rates and the potential for top-down control by an abundant herbivorous copepod, Parvocalanus crassirostris , on the prochlorophyte. Those grazing rates were lower than the rates on a palatable alternative algal food, Isochrysis galbana , when both algal species were presented in monocultures with identical densities. Grazing on the prochlorophyte decreased or ceased at densities over 4.8 × 10 5 cells ml –1 . When the prochlorophyte and the palatable alternative each comprised half of the total density, both species were consumed, but grazing on I. galbana was reduced compared to the grazing rates in a monoculture of this species, especially at higher cell densities. Copepod mortality was observed in treatments with high concentrations of the prochlorophyte, and these treatments contained mucilage. Experiments simulating viscosities produced by prochlorophyte mucilage yielded results consistent with the original grazing experiments (i.e., copepods showed lower grazing rates and higher mortality rates in higher viscosity treatments). Results reveal potential limitations of top-down controls by this grazer on prochlorophyte blooms and HABs that produce mucilage.

Grazing by the Copepod Parvocalanus crassirostris on Picochlorum sp. at Harmful Bloom Densities and the Role of Particle Size - Xiao Ma; Charles A. Jacoby; Kevin B. Johnson (Frontiers in Marine Science, 2021)
Harmful blooms of nanophytoplankton (2–20 μm) are increasingly common and sometimes severe, but requirements and controls of such blooms (e.g., water quality constraints, requirements for nutrients, and the presence of different guilds of grazers) are poorly understood. Laboratory grazing experiments were conducted to evaluate the potential for top-down control by the copepod Parvocalanus crassirostris on a small harmful algal species (an unidentified chlorophyte Picochlorum , 1–4 μm) and to test the effects of cell sizes on grazing rates. The Picochlorum sp. is a strain isolated from a long-lasting harmful algal bloom in the Indian River Lagoon that reached high densities (>1 × 10 6 cells ml –1 ). Experiments contrasted grazing on Picochlorum sp. with grazing on the palatable prymnesiophyte Isochrysis galbana (4–6 μm) in monocultures and mixed cultures. When presented in monocultures, grazing rates on Picochlorum sp. were lower than grazing rates on the palatable alternative. When Picochlorum sp. were presented alongside I . galbana , copepods essentially ceased feeding on the former. In additional experiments, P . crassirostris were fed plastic beads with diameters of 2.0–17.9 μm to control for differences in taste, toxicity, production of mucilage and shape of potential food. Paracalanus crassirostris fed most efficiently on beads with diameters of 7.0–7.9 μm. Results revealed that P . crassirostris can consume Picochlorum sp., but small size and the presence of palatable cells reduces the likelihood of top-down control of blooms of Picochlorum sp.

Understanding Persistent Non-compliance in a Remote, Large-Scale Marine Protected Area - Claire Collins; Ana Nuno; Annette Broderick; David J. Curnick; Asha de Vos; Thomas Franklin; David M. P. Jacoby; Chris Mees; James Moir-Clark; John Pearce; Tom B. Letessier (Frontiers in Marine Science, 2021)
Area coverage of large-scale marine protected areas (MPAs) (LSMPAs, > 100,000 km 2 ) is rapidly increasing globally. Their effectiveness largely depends on successful detection and management of non-compliance. However, for LSMPAs this can be difficult due to their large size, often remote locations and a lack of understanding of the social drivers of non-compliance. Taking a case-study approach, we review current knowledge of illegal fishing within the British Indian Ocean Territory (BIOT) LSMPA. Data stemming from enforcement reports (2010–20), and from fieldwork in fishing communities (2018–19) were combined to explore and characterise drivers of non-compliance. Enforcement data included vessel investigation reports ( n = 188), transcripts of arrests (20) and catch seizures (58). Fieldwork data included fisher interviews (95) and focus groups (12), conducted in two communities in Sri Lanka previously associated with non-compliance in BIOT LSMPA. From 2010 to 2020, there were 126 vessels suspected of non-compliance, 76% of which were Sri Lankan. The majority of non-compliant vessels targeted sharks (97%), catching an estimated 14,340 individuals during the study period. Sri Lankan vessels were primarily registered to one district (77%) and 85% operated from just two ports within the fieldwork sites. Social Network Analysis (SNA) showed that 66% of non-compliant vessels were linked by social ties, including sharing crew members, compared with only 34% of compliant vessels. Thematic analysis of qualitative data suggested that perceptions of higher populations of sharks and social ties between vessels may both be important drivers. We discuss our findings within a global context to identify potential solutions for LSMPA management.

In Reply: “On Insulin Kinetics Following High-Dose Insulin Therapy, and When to Stop Therapy” - Justin N. Corcoran; Katherine J. Jacoby; Travis D. Olives; Stacey A. Bangh; Jon B. Cole (Journal of Medical Toxicology, 2021)

Behavior and Ecology of Silky Sharks Around the Chagos Archipelago and Evidence of Indian Ocean Wide Movement - David J. Curnick; Samantha Andrzejaczek; David M. P. Jacoby; Daniel M. Coffey; Aaron B. Carlisle; Taylor K. Chapple; Francesco Ferretti; Robert J. Schallert; Timothy White; Barbara A. Block; Heather J. Koldewey; Ben Collen (Frontiers in Marine Science, 2020)
Silky sharks ( Carcharhinus falciformis ) represent a major component of global shark catch, both directly and as bycatch, and populations are declining as a result. An improved understanding of their movement ecology is needed to support conservation efforts. We deployed satellite and acoustic tags (2013–2018) and analyzed historical fisheries records (1997–2009), to investigate the spatial ecology of silky sharks in the central Indian Ocean and a large Marine Protected Area (MPA; 640,000 km 2 ) around the Chagos Archipelago. We observed high fidelity to the MPA, and a sustained diurnal association with a seamount complex, with individuals moving off at night and returning at sunrise. Yet, we also observed large-scale divergent movements in two satellite tagged individuals and documented the furthest recorded displacement distance for a satellite tagged silky shark to date, with one individual moving from the MPA to the Kenyan coast—a displacement distance of 3,549 km (track distance ∼4,782 km). Silky sharks undertook diel vertical migrations and oscillatory diving behavior, spending > 99% of their time in the top 100 m, and diving to depths of greater than 300 m, overlapping directly with typical deployments of purse seine and longline sets in the Indian Ocean. One individual was recorded to a depth of 1,112 m, the deepest recorded silky shark dive to date. Individuals spent 96% of their time at liberty within water temperatures between 24 and 30°C. Historic fisheries data revealed that silky sharks were a major component of the shark community around the archipelago, representing 13.69% of all sharks caught by longlines before the fishery closed in 2010. Over half (55.88%) of all individuals caught by longlines and purse seiners were juveniles. The large proportion of juveniles, coupled with the high site fidelity and residence observed in some individuals, suggests that the MPA could provide considerable conservation benefits for silky sharks, particularly during early life-history stages. However, their high mobility potential necessitates that large MPAs need to be considered in conjunction with fisheries regulations and conservation measures in adjacent EEZs and in areas beyond national jurisdiction.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Persistent Hyperinsulinemia Following High-Dose Insulin Therapy: A Case Report - Justin N. Corcoran; Katherine J. Jacoby; Travis D. Olives; Stacey A. Bangh; Jon B. Cole (Journal of Medical Toxicology, 2020)

Conserve the eco-evolutionary dynamic, not the subspecies: phenological divergence and gene flow between temporal cohorts of Euphilotes ancilla endemic to southern Nevada - Daniel B. Thompson; Kevin McKelvey; Paul van Els; Gretchen Andrew; Paula Jacoby-Garrett; Matt Glenn; Corey Kallstrom; Kristine L. Pilgrim; Paul A. Opler (Conservation Genetics, 2020)

The last millennium largest floods in the hyperarid Kuiseb River basin, Namib Desert - T. GRODEK; G. BENITO; B. A. BOTERO; Y. JACOBY; N. PORAT; I. HAVIV; G. CLOETE; Y. ENZEL (Journal of Quaternary Science, 2013)
The largest Kuiseb River floods initiate at the basin's semi‐arid headwater. Downstream, along the hyperarid Namib Desert, these floodwaters are feeding shallow alluvial aquifers, the only available water for human activity and for the natural ecology. Here, we characterize the largest floods and their changing frequency and magnitudes using palaeohydrological methods. Along 120 km of the rivers canyon 35 palaeoflood deposit sites were identified. At five of these sites we conducted stratigraphic and geochronological analyses and flood discharge estimations. The upper bound of the largest flood over the late Holocene is ∼1475 m 3 s −1 . Over the last 1300 years more than ten floods have exceeded 1250 m 3 s −1 . An additional 33 floods exceeded 400 m 3 s −1 . The last millennium was characterized by one large flood every 30–40 years during the periods 1250–1335, 1355–1565 and 1715 AD to the present. A slight increase in flood frequency (not magnitude) occurred during 1565–1715 AD (one large flood in ∼20 years) and during two short episodes, 1185–1205 and 1335–1355 AD (seven and four floods in 20 years, respectively). These episodes of increased flood frequency are associated with other proxy records of higher water availability in the Namib. Copyright © 2013 John Wiley & Sons, Ltd.

The role of relatedness in structuring the social network of a wild guppy population - Darren P. Croft; P. B. Hamilton; S. K. Darden; D. M. P. Jacoby; R. James; E. M. Bettaney; C. R. Tyler (Oecologia, 2012)

The effect of IM Droperidol on driving performance - Jessica Fulton; Gary Popovetsky; Jeanne L. Jacoby; Michael B. Heller; James Reed (Journal of Medical Toxicology, 2006)

Modeling the Economic Response to Global Climate Change - Alain B. Haurie; Henry D. Jacoby; Laurent Viguier (Environmental Modeling & Assessment, 2003)

Remote Sensing And Surface Observations Of The Response Of The Atmospheric Boundary Layer To A Solar Eclipse - Fanny Girard-Ardhuin; B. Bénech; B. Campistron; J. Dessens; S. Jacoby-Koaly (Boundary-Layer Meteorology, 2003)

Turbulent Dissipation Rate In The Boundary Layer Via UHF Wind Profiler Doppler Spectral Width Measurements - Sandra Jacoby-Koaly; B. Campistron; S. Bernard; B. Bénech; F. Ardhuin-Girard; J. Dessens; E. Dupont; B. Carissimo (Boundary-Layer Meteorology, 2002)

The 18th congress of the israeli phytopathological society - Y. Elad; D. Shtienberg; H. Vintal; Y. Cohen; Sonia Farkash; Zipora Reshit; A. Baider; Edna Levy; I. S. Ben-Ze’ev; Y. Nitzani; Frieda Kleitman; Talma Katan; et al. (Phytoparasitica, 1997)

Persistence of rat parvovirus in athymic rats - Diane J. Gaertner; R. O. Jacoby; Abigail L. Smith; Rachel B. Ardito; F. X. Paturzo (Archives of Virology, 1989)

Persistence of rat virus in seropositive rats as detected by explant culture - F. X. Paturzo; R. O. Jacoby; P. N. Bhatt; Abigail L. Smith; Diane J. Gaertner; R. B. Ardito (Archives of Virology, 1987)